Australian firefighters perceptions of heat stress, fatigue and recovery practices during fire-fighting tasks in extreme environments. (September 2021) - Fullagar, Hugh H.K.; Schwarz, Edgar; Richardson, Andrew; Notley, Sean R.; Lu, Donna; Duffield, Rob
Abstract: Objectives: The aim of this study was to assess current perceptions of heat stress, fatigue and recovery practices during active duty in Australian firefighters. Design: Prospective survey. Methods: 473 firefighters from Fire and Rescue New South Wales completed a two-part, 16-item survey. Questions included perceptions of the operational activities and body areas associated with the most heat stress, the most mentally and physically demanding activities, and levels of fatigue felt. Further questions focussed on the use and importance of recovery practices, effectiveness of currently used heat-mitigation strategies and additional cooling strategies for future use. Results: Around a third of firefighters (62%) reported structural fire-fighting as the hottest operational activities experienced, followed by bushfire-fighting (51%) and rescue operations (38%). The top three responses for which body-parts get the hottest ranked as 'the head' (58%), 'the whole body' (54%) and 'the upper back' (40%), respectively. The majority of firefighters ( 90%) stated they always or sometimes use the opportunity to recover at an incident, with the top three being 'sit in the shade' (93%), 'cold water ingestion (drinking)' (90%) and 'removing your helmet, flash hood and jacket' (89%). Firefighters reported higher usefulness for more easily deployed strategies compared to more advanced strategies. Limited age and gender differences were found, although location of active service differences were present. Conclusion: These findings may inform future research, and translation to operational directives for recovery interventions; including exploration of protective gear and clothing, education, resources and provision of cooling methods, as well as recovery aid development.